TINJAUAN YURIDIS KEWAJIBAN PENDAFTARAN USAHA BAGI PELAKU USAHA E-COMMERCE MENURUT UNDANG-UNDANG NOMOR 7 TAHUN 2014 TENTANG PERDAGANGAN - Andryan Aprynaldi; Diding Rahmat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN, 2024)
This research aims to explore the obligation of business registration for e-commerce players based on Law Number 7 Year 2014 concerning Trade. This study employs a normative legal research approach utilizing statute and conceptual approaches. Secondary data is utilized, and the method of data collection employed is literature research. The research findings discuss e-commerce trade license regulations encompassing various policies within legislation such as the Trade Law, the Electronic Information and Transactions Law (ITE Law), and the Consumer Protection Law. The study also highlights the importance of mandatory company registration to prevent conflicts, with the application of sanctions for businesses that violate these provisions.